Serum procalcitonin as diagnostic marker for postoperative surgical wound infection - Dr. Manmeet Kaur Gill; Dr. Sahiba Kukreja (Tropical Journal of Pathology and Microbiology, 2019)
Background: Early diagnosis and treatment of postoperative infections is important to curtail the morbidity and economic burden associated with them. Currently there is no reliable diagnostic markers to differentiate infectious cause of postoperative fever from non-infectious one. The effectiveness of serum procalcitonin in establishing the same was investigated.Method: It was a cross-sectional study in which 100 consecutive patients who had onset of fever within seven days of the surgery were evaluated. These patients were divided into two groups of 50 each. Group A comprised of 50 patients having fever and elevated TLC (total leukocyte count) & ANC (absolute neutrophil count). Group B had 50 patients having fever but with normal TLC and ANC. All patients were assessed for C-reactive protein level, and serum procalcitonin and wound condition. Patients who had unhealthy wounds, their wound swabs were sent for microbiological work up.Results: 11/50 patients had raised serum procalcitonin levels in group A whereas in group B none had abnormal PCT levels. The statistical analysis showed that this difference was statistically significant as p value was <0.05. There was also statistically significant relation between PCT and wound condition. All patients with unhealthy wound were culture positive and also had raised raised serum procalcitonin levels. However, CRP was raise in patients in both the groups (96/100) which was found to be statistically insignificant with P value =0.307.Conclusion: Serum procalcitonin is a helpful biomarker marker in differentiating infectious from noninfectious causes of postoperative fever and can be used as an adjunct with clinical and microbiological findings.